Caracterização dos cnidários pelágicos associados à pesca de arrasto de camarão na Plataforma Continental Amazônica - MARINHO, Yago Brito (2020)
Associated fauna is defined as the individuals, from any species and size spectrum, which are accidentally capture with the fishery target species. One of the components of the associated fauna from trawling fisheries are some species of jellyfish, organisms composed mainly by water (95%) and with a pelagic to bento-pelagic nature. The objective of this study was to describe the jellyfish composition (classes Scyphozoa and Cubozoa), besides the estimation of density and biomass from length-weight regression for the dominant species from the associated fauna of the shrimp trawling fisheries at some regions from the Brazilian Amazon shelf. Samples were obtained from three campaigns which occurred during August to September 2016, April to May and June to July 2017, through bottom net trawling and kept separately in plastic bags inside recipient containing neutralized, seawater diluted formaldehyde (final concentration of 4%). In the laboratory taxonomic identification and biometry were performed. Only two species were identified: Chiropsalmus quadrumanus and Stomolophus meleagris. Density was calculated through the number of individuals estimated at each campaign, divided by the volume of filtered water in each trawl. At last, biomass was estimated from the density of each trawl, multiplied by the average jellyfish weight, acquired through the use of length-weight regressions available at literature. The length and weight values showed significant variation between the rainy and dry season. Only two species were identified: Chiropsalmus quadrumanus and Stomolophus meleagris. Both species during the dry season had lower biomass values (average 49.4 ± 26.5 g and 94.8 ± 55.5 g for C. quadrumanus and S. meleagris respectively) compared to the rainy season (average is 57.9 ± 21.2 g and 194.6 ± 75.3 g for C. quadrumanus and S. meleagris respectively). During the dry season, although smaller, the individuals were more abundant (C. quadrumanus 4,103 ind.km-3 and S. meleagris 3,7x102 ind.km-3). In the rainy season, the animals were larger and less abundant (C. quadrumanus 3,6x103 ind.km-3 and S. meleagris 2,6x102 ind.km-3). The spatial differences between the campaigns were not significant, although the density was higher for campaign 1, farther from the coast, while the campaigns 2 and 3 were closer to the coast, with lower density. This work was the first to study the biomass and density of pelagic cnidaria on the Amazon Continental Shelf and shows its variability in relation to time.